Studies in Australian Tettigoniidae: Three New Species of Agraeciini From North-eastern Australia Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini - Rentz, Dcf; Su, You Ning (Zootaxa, 2019)
Three agraeciine species are described from the north-eastern tropics of coastal Queensland. Two species of Austrosalomona are described. A. destructor sp. nov. is common from the Daintree region to Cairns where it has been seen to destroy orchids and other garden flowers. A. poecila has been found on coastal islands as well as at a few localities on the mainland north of Cairns. It has not been implicated in any destructive activities. Salomona nori sp. nov. is known from Kutini-Payamu (Iron Range) where it has been found living in tree holes. It is a large and formidable species that attracts the attention of tourists. Karyotypes and acoustic information are presented for all three species.